Defining the optimal threshold and prognostic utility of pre-treatment hemoglobin level as a biomarker for survival outcomes in head and neck cancer patients receiving chemoradiation. (October 2022) - Ma, Sung Jun; Yu, Han; Khan, Michael; Yu, Brian; Santhosh, Sharon; Chatterjee, Udit; Gill, Jasmin; Iovoli, Austin; Farrugia, Mark; Wooten, Kimberly; Gupta, Vishal; McSpadden, Ryan; et al.
Highlights: The optimal threshold of anemia for head and neck cancer patients is unclear. Threshold of anemia was determined to be hemoglobin of 11.4. Anemia was associated with worse overall and progression-free survival outcomes. Anemia was prognostic for survival among patients with HPV-negative tumors. Abstract: Objectives: We sought to define the optimal threshold for anemia in North American head and neck cancer patients and evaluate its role as a prognostic biomarker. Materials and Methods: A single-institution database was queried for patients with head and neck cancer who underwent chemoradiation from January 2005 to April 2021. An optimal threshold of hemoglobin (Hgb) level was defined based on maximum log-rank test statistic. Cox multivariable analysis (MVA), Kaplan-Meier, and propensity score matching were performed to evaluate treatment outcomes. Results: A total of 496 patients were identified. Threshold for Hgb was determined to be 11.4 for both overall survival (OS) and progression-free survival (PFS). Low Hgb was associated with worse OS (adjusted hazards ratio [aHR] 2.41, 95 % confidence interval [CI] 1.53–3.80, p < 0.001) and PFS (aHR 2.01, 95 % CI 1.30–3.11, p = 0.002). Similar findings were observed among 39 matched pairs for OS (5-year OS 22.3 % vs 49.0 %; HR 2.22, 95 % CI 1.23–4.03, p = 0.008) and PFS (5-year PFS 24.3 % vs 39.1 %; HR 1.78, 95 % CI 1.02–3.12, p = 0.04). Among those with HPV-negative tumors, low Hgb was associated with worse OS (aHR 13.90, 95 % CI 4.66–41.44, p < 0.001) and PFS (aHR 5.24, 95 % CI 2.09–13.18, p < 0.001). However, among those with HPV-positive tumors, low Hgb was not associated with both OS (aHR 1.75, 95 % CI 0.60–5.09, p = 0.31) and PFS (aHR 1.13, 95 % CI 0.41–3.14, p = 0.82). Conclusion and relevance: Low Hgb below 11.4 was an independent adverse prognostic factor for worse survival. It was also prognostic among patients with HPV-negative tumors, but not for HPV-positive tumors.